2013
DOI: 10.1108/08876041311309252
|View full text |Cite
|
Sign up to set email alerts
|

Encounter-based antecedents of e-customer citizenship behaviors

Abstract: Purpose – In the marketing and consumer behavior literature, much remains to be explained about customer citizenship behavior in a highly technological e-retailing context. The purpose of this paper is to present the results of a survey of 186 e-shoppers which was conducted grounded in the social exchange theory. Design/methodology/approach – Structural equation modeling is used to test the proposed model. Findings – The results provide support that e-customer familiarity with an e-store and facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
92
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 55 publications
10
92
1
5
Order By: Relevance
“…Consistent with past research (Anaza & Zhao, ; Chen, Chen, & Farn, ; Groth, ; Yi & Gong, ), this study argues that customer satisfaction positively influences customer citizenship behaviors. Groth (), for instance, found that customers satisfied with the services provided by a business were more inclined to recommend the business to family and friends, help other customers with their shopping needs, and provide feedback to the company and its employees.…”
Section: Conceptual Framework and Hypotheses Developmentsupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with past research (Anaza & Zhao, ; Chen, Chen, & Farn, ; Groth, ; Yi & Gong, ), this study argues that customer satisfaction positively influences customer citizenship behaviors. Groth (), for instance, found that customers satisfied with the services provided by a business were more inclined to recommend the business to family and friends, help other customers with their shopping needs, and provide feedback to the company and its employees.…”
Section: Conceptual Framework and Hypotheses Developmentsupporting
confidence: 87%
“…Identified by terms such as customer organizational citizenship behaviors (Bove et al., ), customer extra‐role behaviors (Ahearne, Bhattacharya, & Gruen, ), customer discretionary behaviors (Ford, ), customer helping behaviors (Johnson & Rapp, ), and customer voluntary performance (Bettencourt, ), these behaviors are believed to fall outside the role and expectations of what customers are required to do before, during, and after the acquisition of a product or service. Stemming from Groth's () definition, Anaza and Zhao () purport that online shoppers who engage in positive extra‐role behaviors are classified as good online citizens because their actions help online retailers improve overall service delivery to online shoppers. Because online service encounters require customers to become partial employees in the production of their own services (e.g., self‐booking a hotel reservation online rather than using a travel agent), the willingness of a customer to go beyond their prescribed in‐role expectation, by exhibiting gestures that benefit both the firm and other consumers, suggest that these customers are committed to seeing the online retailer succeed.…”
Section: Personality Traits Empathy and Customer Citizenship Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between CCB and satisfaction has been analyzed in numerous studies (Anaza, & Zhao, ; Groth, ; Vega‐Vázquez, Revilla‐Camacho, and Cossío‐Silva, ; Yi, & Gong, ). Most studies have revealed a significant direct effect of satisfaction on CCB.…”
Section: Definition Of Concepts and Hypothesesmentioning
confidence: 99%
“…The demand for improvements has resulted in speeding up the supply process such as the use of web-based solutions (Anaza and Zhao, 2013). But the supply side has needed to respond to more efficient and effective methods of delivery from the producer through to the final destination (Forsberg and Towers, 2007).…”
Section: Introductionmentioning
confidence: 99%